2021
DOI: 10.1371/journal.pone.0261488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine proteome among rat models by intraperitoneal injection with single bacteria and co-injection with two bacteria

Abstract: Purpose To explore and compare urine proteome changes among rat models by intraperitoneal injection with single bacteria and co-injection with two bacteria. Method Escherichia coli and Staphylococcus aureus are two common human pathogens. Three rat models were established: (i) the intraperitoneal co-injection of E. coli and S. aureus model (ES model), (ii) intraperitoneal injection of E. coli model (E model), and (iii) intraperitoneal injection of S. aureus model (S model). Urinary proteomes on days 0, 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…A change in the urinary proteome was also established during infection of the abdominal cavity with Escherichia coli and Staphylococcus aureus. It was shown that their combined presence causes significant differences from a monoinfection [ 36 ]. Based on these findings, it may be possible to assess the effect of an infectious agent on the composition of urine, including volatile metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…A change in the urinary proteome was also established during infection of the abdominal cavity with Escherichia coli and Staphylococcus aureus. It was shown that their combined presence causes significant differences from a monoinfection [ 36 ]. Based on these findings, it may be possible to assess the effect of an infectious agent on the composition of urine, including volatile metabolites.…”
Section: Introductionmentioning
confidence: 99%